Weak Investment Poses a Threat to Industry in Europe - Martin Gornig; Alexander Schiersch (Intereconomics, 2016)
The global industrial structure has been in a constant state of change for some time now. While China's share has steadily grown, Western industrialised countries have mostly experienced losses in industrial market share. Within Europe, the fates of the established industrialised nations have all played out very differently. For example, France and the UK have suffered massive losses, while Germany was able to noticeably re-expand production following the 2009 crisis. Industry in Europe is likely to fall further behind in the coming years — not only to catching-up countries like China, but also to other industrialised nations. The US, for example, exhibits far more dynamic industrial investment, outpacing not only France and the UK but also Germany.
Keywords: 330